Benefiting from additive manufacturing for mass customization across the product life cycle. (2021) - Lacroix, Rachel; Seifert, Ralf W.; Timonina-Farkas, Anna
Abstract: Additive manufacturing (AM) was initially designed for prototyping and product personalization, where high production quantities were not required. Now, it is also implemented for final part production to achieve cost-effective mass customization (MC). Thanks to its tool-less production and extreme flexibility, AM has the potential to address individual customer preferences with custom final parts. Nevertheless, despite its increased competitiveness, AM is not yet likely to replace traditional MC systems, but it can complement them, improving manufacturing efficiency. To broaden our understanding of how AM can complement traditional manufacturing systems, we develop an exploratory quantitative model. First, we leverage customer-centricity in a novel time-varying locational choice model of heterogeneous customers, coupling the Bass and the Hotelling–Lancaster models. Then, we investigate customer-centric marketing and operations decisions, exploring technology-switching scenarios that interchange AM with MC across the product life cycle (PLC). We formulate and solve an optimization problem by jointly deciding on technology-switching times, pricing, and product variety strategies to maximize a manufacturer's profit and meet individual customers' diverse and evolving needs. We use a validated Sample Average Approximation approach for the numerical solution of our non-convex optimization problem. Testing different pricing strategies, we show that decreasing and flexible trajectories are optimal. We derive analytical properties for the optimal pricing policy and demonstrate that a manufacturer can benefit from interchanging AM and MC across the PLC, in particular by adopting an AM-MC-AM scenario. Highlights: Adopting a hybrid manufacturing practice can lead to a significant profit surplus. AM can address product variants and time-sensitive customers during the PLC. MC provides economies of scale and satisfies customers during the PLC growth stage. Combining AM with traditional MC can be preferable over the sole use of AM. Pricing flexibility policy allows to capture certain customer purchasing profiles.